Effect of historical residual hexachlorocyclohexanes and dichlorodiphenyltrichloroethane on bacterial communities in sediment core collected from an estuary in northeastern China by next-generation sequencing. Issue 1 (15th April 2015) - Guo, Jianguo; Zhao, Longhao; Lu, Weihong; Jia, Hongliang; Wang, Luo; Liu, Xianjie; Sun, Yeqing
Highlights: o, p′-DDT, o, p′-DDD, and depth had important influences on bacterial community. o, p′-DDD had a greater influence on sediment-dwelling bacteria than o, p′-DDT. H′ was significantly negatively correlated with total HCHs and DDTs. Flavobacteria and Clostridia content can be considered an indicator of pollution. Abstract: In this study, we evaluate the influence of hexachlorocyclohexanes (HCHs) and dichlorodiphenyltrichloroethane (DDT) on bacterial communities of sediment core from an estuary formed during the period of 1960–2011. Canonical correspondence analysis showed that o, p′-DDT, o, p′-DDD (mitotane), and depth had important influences on bacterial community distributions ( p < 0.05). Furthermore, our results found variance explained by all variables was 82.9%, while that by o, p′-DDD was 24.4%, and that of o, p′-DDT was 9.8%, indicating that o, p′-DDD had a greater influence on sediment-dwelling bacteria than o, p′-DDT. Also, bacterial diversity was affected and the Shannon index was significantly negatively correlated with total HCHs ( r = −0.579, p < 0.05) and total DDTs ( r = −0.607, p < 0.01), respectively. Furthermore, our results showed that Flavobacteria and Clostridia content can be considered an indicator of pollution of HCHs and DDTs in sediment core samples.